Diversity study among Guinea grass (Megathyrsus maximus Jacq.) (Poales: Poaceae) genotypes and development of a core germplasm set. Issue 6 (1st December 2020) - Roy, A. K.; Malaviya, D. R.; Kaushal, P.; Mahanta, S. K.; Tewari, R.; Chauhan, R.; Chandra, A.
Abstract: Guinea grass ( Megathyrsus maximus Jacq.) is an important forage species in vast rangelands/grasslands of India and several tropical countries owing to its high biomass yield, good nutritional quality and wide adaptation. Evaluation of the existing natural variation and selection of desirable genotypes is the most plausible breeding method for this apomictic and polyploid grass. Developing a core sub-set to narrow down the number of germplasm required for future genetic studies is also pertinent. The present study involved characterization of 152 diverse M. maximus germplasm representing collections from different agro-ecological zones of India as well as those procured from Africa and Brazil; and development of a core sub-set. Nineteen metric, seven non-metric and nine nutritive traits together established the presence of wide variability among the genotypes. Clustering of the genotypes resulted in eight distinct clusters. The largest cluster included genotypes from Ethiopia, north India, north-western India, south India and north-eastern hill region, thus represented the highest diversity. Eleven of the total 26 Ethiopian genotypes clustered together. Non-metric morphological traits effectively differentiated the genotypes, and were associated with nutritional quality also. Genotypes which flowered once in a year showed slightly better crude protein and digestibility. The clusters were further sub-clustered and representatives were selected to develop the core sub-set of 23 genotypes comprising 20 indigenous and three exotic accessions. Comparison of the range of diversity and mean value for traits as obtained in the core sub-set and that in the total germplasm indicated successful capturing of maximum diversity in the core sub-set.